1991
DOI: 10.1007/bf00405002
|View full text |Cite
|
Sign up to set email alerts
|

Insulin prevents adoptive cell transfer of diabetes in the autoimmune non-obese diabetic mouse

Abstract: Early intensive insulin treatment is thought to improve subsequent Beta-cell function in Type 1 (insulin-dependent) diabetic patients. Prophylactic insulin administration also reduced diabetes incidence in diabetes-prone animals. To study the mechanisms by which these effects occur, we tested the ability of insulin therapy in the model of non-obese-diabetic mice, to prevent the penetration of committed T cells into the islets and subsequent Beta-cell destruction. Sublethally irradiated non-obese-diabetic males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 22 publications
6
24
0
Order By: Relevance
“…With regard to the progression of insulitis in the NOD mouse, we confirmed the effect of prophylactic insulin treatment in lowering the severity of destructive insulitis [13,14]. Moreover, we showed that if the effect of the treatment on the infiltrative lymphocytic insulitis, as assessed by H+E staining, was not detectable at 9 weeks of age, it became clearly visible and significant at 13 weeks of age.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…With regard to the progression of insulitis in the NOD mouse, we confirmed the effect of prophylactic insulin treatment in lowering the severity of destructive insulitis [13,14]. Moreover, we showed that if the effect of the treatment on the infiltrative lymphocytic insulitis, as assessed by H+E staining, was not detectable at 9 weeks of age, it became clearly visible and significant at 13 weeks of age.…”
Section: Discussionsupporting
confidence: 63%
“…The same improvement was observed in different animal models of type 1 diabetes, either induced by neonatal streptozotocin [9], or the spontaneous models, the BB rat [10][11][12] and the NOD mouse [13]. In both the BB rat and the NOD mouse prophylactic insulin treatment not only prevented spontaneous disease, but transfer of diabetes to young pre-diabetic animals was also inhibited [14,15].…”
Section: Introductionsupporting
confidence: 58%
“…The same caveat applies to mouse adoptive transfer models, which documented a similar protective effect, but with no off-treatment follow-up period [25,26]. Indeed, in the study by Thivolet et al [26] protection was associated with significant hypoglycaemia, similar to the values we observed, and was lost upon early treatment discontinuation.One major question remains unanswered: by which mechanisms does β-cell rest exert its protective effect? Two major hypotheses can be proposed.…”
supporting
confidence: 72%
“…Cell-mediated responses to insulin in peripheral blood are weak [6][7][8][9][10][11][12][13], but insulinspecific T cell clones isolated from animal models of diabetes have been shown to transfer disease [14]. Moreover, treatments with intravenous, subcutaneous, oral or intranasal insulin have been shown to prevent or delay disease onset in animals and in humans [15][16][17][18][19]. Thus insulin, or its prohormone proinsulin, is considered an important early autoimmune target in type 1 diabetes, and has therefore a potential role in antigen-specific immunotherapy [20].…”
Section: Introductionmentioning
confidence: 99%